Pobreza Vs Desarrollo: poverty vs. development - López González, Silvia Patricia (Derecho Global. Estudios sobre Derecho y Justicia, 2019)
<span style="display: inline !important; float: none; background-color: #f8f9fa; color: #222222; font-family: arial,sans-serif; font-size: 28px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: pre-wrap; word-spacing: 0px;">The biggest challenge facing the world is the fight against poverty, we know that in Latin America 184 million people live in poverty, which is equivalent to 30.2% of the population; 62 million of them, that is, 10.2% do so in extreme poverty, these data place us as the most unequal region in the world. (ECLAC 2018) In relation to Mexico, there are 52.4 million poor people and the entity with the largest number is the State of Mexico with 7.5 million people; they follow him on the painful list of the most impoverished states: Chiapas with 76.4%; Guerrero with 66.5%; Oaxaca 66.4.%; Veracruz